Conforming to Belong vs Resisting to Remain in Laila Lalami’s Hope and Other Dangerous Pursuits and Shaila Abdullah’s Saffron Dreams - Anya Cahya Kirani; M. Irfan Zamzami (J-Lalite: Journal of English Studies, 2026)
This study examines the process of Muslim female identity formation through a comparative reading of the characters Faten in Laila Lalami's novel Hope and Other Dangerous Pursuits (2005) and Arissa in Shaila Abdullah's novel Saffron Dreams (2009). Responding to the tendency of existing research to view identity as an end result, a form of resistance, or a social position, this study addresses the relative lack of attention to how identity is gradually formed throughout the characters' life journeys. This study integrates Muslimah Narratives, the Bildungsroman, and Postcolonial Feminism to examine character development, diasporic experiences, religious identity, and colonial power relations in shaping the characters' identities across different diasporic contexts. The findings reveal two contrasting patterns of identity formation. Faten represents a negative Bildungsroman, in which religious idealism and personal agency are gradually eroded by economic uncertainty, illegal migration, and patriarchal-colonial power structures, resulting in self-disruption and arrested maturation. In contrast, Arissa exemplifies a transcultural Bildungsroman, in which trauma, Islamophobia, and loss become catalysts for emotional and spiritual growth through reflective religiosity and narrative agency, particularly through writing. This comparative analysis demonstrates that the identities of Muslim women in the diaspora are neither static nor homogeneous; rather, they are shaped by legal status, material conditions, and access to symbolic spaces of agency. This study contributes to a deeper understanding of Muslim women's identity formation in diasporic contexts and highlights the subjectivity of Muslim women's literature beyond reductive stereotypes of victimhood or resistance.